Resilience of Jakarta’s Performing Arts Studios: A THIO Analysis of Digital Technology in the Creative Ekonomi - Denta Mandra Pradipta Budiastomo; Ida Ayu Trisnawati; I Gusti Putu Sudarta; Ni Made Arshiniwati (Dinasti International Journal of Education Management And Social Science, 2025)
Many things have altered as a result of the rise of information and communication technology, and society's transition to the digital age. Advances in digital technology have transformed how performing arts studios understand and produce works of art. The purpose of this study is to determine the value of the contribution of performing arts studios in running their businesses, as well as solutions in choosing digital technology in art activities. This research is quantitative; the sample in this study was 30 respondents. This figure was derived from five performing arts enterprises, each representing six areas in DKI Jakarta, together with input from eight experts. The analysis technique used in the research uses THIO (Technology, Human, Information, Organization) analysis and creative economy theory. This study's findings indicate a Technology Contribution Coefficient (TCC) of 0.339 for the use of digital technology in performing arts studios in Jakarta, categorized as a reasonable value.